SPE Western Regional Meeting 1992
DOI: 10.2118/24059-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for the Analysis of Closed-Chamber Tests

Jinjiang Xiao,
A. C. Reynolds

Abstract: SPE Members Abstract A closed chamber test (CCT) is characterized by a variable wellbore storage coefficient, whereas, in a slug test, the wellbore storage coefficient is assumed to be constant. It is shown that for ranges of parameters often encountered in practical cases, a large span of the CCT pressure data can be converted to equivalent slug test pressure data which can then be analyzed by several available slug test analysis techniques. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many authors have addressed various analytical methods of dealing with slug-test or closed-chamber data. 7,8,9 Although most of these analytical procedures were developed for drill-stem testing, several papers have been presented showing early applications of this method in rod-pumping wells.…”
Section: Slug Testing Methodsmentioning
confidence: 99%
“…Many authors have addressed various analytical methods of dealing with slug-test or closed-chamber data. 7,8,9 Although most of these analytical procedures were developed for drill-stem testing, several papers have been presented showing early applications of this method in rod-pumping wells.…”
Section: Slug Testing Methodsmentioning
confidence: 99%
“…Recently, Xiao and Reynolds 5 presented new techniques for the analysis of closed chamber tests (CCT) in reservoirs containing a single-phase, slightly compressible fluid of constant compressibility and viscosity. It was demonstrated that a new form of pseudotime can be used to correlate closed-chamber test results with slug test solutions, and thus, data from closed-chamber tests can be analyzed using slug-test type curves and, after performing a simple data transformation, the wellbore storage and skin pressure and pressure derivative type curves.…”
Section: Introductionmentioning
confidence: 99%